Hands-on workshop on the basic of histological analysis / Dr. Siti Syairah Mohd Mutalip and Dr. Gurmeet Kaur Surindar Singh - Mohd Mutalip, Siti Syairah; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
The Histology Unit, Faculty of Pharmacy, UiTM Puncak Alam successfully organised the 'Hands-On Workshop on the Basics of Histological Analysis' on May 25, 2023. The one-day workshop was attended by participants from the different faculties and institutions of UiTM including the Faculty of Pharmacy, Faculty of Health Sciences and Hospital Al-Sultan Abdullah. This workshop aimed to provide opportunities for participants to learn the techniques and histological data analysis that can be used in research. It involved the theory of the principles of histology as well as the hands-on practise of the steps in histological analysis. Besides, it also aimed to expose participants to the proper handling and use of all equipment used in the histology analysis as well as promote the facilities and services offered by the Histology Unit, Faculty of Pharmacy, to potential users from other faculties and institutions.